Political Mediations in Andalusia through the book of Moktabs from the news of the people of Andalusia for Ibn Hayyan al-Qurtubi (D.469AH./1076AD.) - Reja, Alaa Hammad (Al-Adab Journal, 2020)
Andalusia was Known for Political Conditions Since the Muslimes entered Andalusia in the Year 92AH/911AD until the end of the Fifth Century AH/atheist Century AD due to the nature of Muslims to Andulsia, the Stage of the formation of Islamic states,and the resistance of Christianity and the stage of the Political events Charactrized by tides between stability and thr struggle for power.At every stage of the Islamic states, there were rebellions against the rulers and wars with the Spanish Kingdoms,as well as, the fusions of envy, with some people wanting to reach the highest rank or simply remove them.So mediations or intercessions were present to the guardians of the matter and those close to the stakeholders in their state or to have a special guidance to the rulers. These mediations different events in which they were intercesded, some of which threatened the security of the dawa,and some of them insulted the ruler for the misbehavior of the senior officials towards their ruling ruler,including the exploitation of their positions to harm others or personal reprisals.These mediations also had a clear effect for many cases these mediations are fairly unfairly ti those who have been harmed by injustice, injustice and punishment. In other cases,they failed because they did reasons,including the magnitude of the event and its dangers to the ruler and the state. And others.And after that prevailed judgment Islamic in the Land of Andalusia, rulers of Muslims them on the difference their names,it has seen Andalus a number of revolutions and rebels the rulers and exit administrators on different office for obedience their rulers,while great the businese of the point of view rulers van which appeared the right of came out for their Masters ranged ben success and failure,as well as led to save the lives of anumber of people ,and some other than not succeed in working adopted on the nature of the mediation and extent of the status of the mediator of governors of it,as well as the nature of the problem or people want to mediate in them.Hence ,the title of our research is the(( Political Mediations in Andalusia through the book of Moktabs from the news of the people of Andalusia for Ibn Hayyan al-Qurtubi ( D.469AH./1076AD.) )), and what led us to address the subject in Andalusia,most studies dealing with mediations or intercessions were associated with the divine or the great image,on the one hand,and on the other hand,the study of medias reflects the various aspects of the political life of Andalusia,such as the extent of the princes and rulers in the implementation of their judgments, the extent of their justice in the release of those entences,and the extent of hrearing the whishpers,and the extent of tolerance towards their enemies and outsiders.Ibn Hayyan al-Qurtubi is one of the Andalusian history of the Muslims in Andalusia in general and the history of the Umayyad state to the succession of the ruler Al-Muntasir Malah in 366AH/967AD in particular. His writings received the approval of historians and modernists despite the loss of most of them.